Heterogeneity and genomic loci of ubiquitous transgenic Cre reporter lines in zebrafish. Issue 10 (2nd June 2022) - Lalonde, Robert L.; Kemmler, Cassie L.; Riemslagh, Fréderike W.; Aman, Andrew J.; Kresoja‐Rakic, Jelena; Moran, Hannah R.; Nieuwenhuize, Susan; Parichy, David M.; Burger, Alexa; Mosimann, Christian
Abstract: Background: The most‐common strategy for zebrafish Cre/ lox ‐mediated lineage labeling experiments combines ubiquitously expressed, lox ‐based Switch reporter transgenes with tissue‐specific Cre or 4‐OH‐Tamoxifen‐inducible CreERT2 driver lines. Although numerous Cre driver lines have been produced, only a few broadly expressed Switch reporters exist in zebrafish and their generation by random transgene integration has been challenging due to position‐effect sensitivity of the lox ‐flanked recombination cassettes. Here, we compare commonly used Switch reporter lines for their recombination efficiency and reporter expression pattern during zebrafish development. Results: Using different experimental setups, we show that ubi:Switch and hsp70l:Switch outperform current generations of the two additional Switch reporters actb2:BFP‐DsRed and actb2:Stop‐DsRed . Our comparisons also document preferential Cre‐dependent recombination of ubi:Switch and hsp70l:Switch in distinct zebrafish tissues at early developmental stages. To investigate what genomic features may influence Cre accessibility and lox recombination efficiency in highly functional Switch lines, we mapped these transgenes and charted chromatin dynamics at their integration sites. Conclusions: Our data documents the heterogeneity among lox ‐based Switch transgenes toward informing suitable transgene selection for lineage labeling experiments. Our work further proposes that ubi:Switch and hsp70l:Switch define genomic integration sites suitable for universal transgene or switch reporter knock‐in in zebrafish. Key Findings: loxP‐based reporters for Cre activity in zebrafish show variable potency ubi:switch and hsp70l:Switch display widespread and reproducible Cre sensitivity Modifying EGFP in ubi:Switch does not alter recombination efficiency Transgene mapping reveals genomic features at Switch reporter integrations